Pelaksanaan Bakti Sosial Pemeriksaan Kesehatan Gratis di Dusun Talle, Desa Bonto Tappalang, Kabupaten Bantaeng Tahun 2021 - Robertus Masyhuri; St.Nurfatul Jannah (PT.Mantaya Idea Batara, 2022)
Community service activities carried out in Talle Hamlet, Bonto Tappalang Village, Bantaeng Regency, Thursday – Saturday, 08:15 – 16.00 WITA, 19 – 21 March 2021 which include free health checks. The purpose of this activity is to detect chronic diseases early and to improve the quality of public health in Dusun Talle, Desa Bonto Tappalang, Kabupaten Bantaeng so that local health instances can immediately further treat patients with chronic diseases. From 50 patients who took part in the free medical check-up that was held, the results obtained were normal blood pressure as many as 20 people, high blood pressure as many as 30 people, Normal uric acid is 50 people and normal blood sugar is 25 people, high blood sugar is 10 people and low blood sugar is 5 people, some of the obstacles in implementing free health care are, there are limitations in supporting facilities for conducting health checks, including limited equipment and health workers conducting health checks so the activities take a long time, the health inspection activity which was planned to run for two days could not be realized optimally because it collided with the activities of the participants, most of them, are farmers, and their activities started from morning to evening. So the socialization team was a bit bothered to adjust the time accordingly